Phosphate solubilization by Pseudomonas fluorescens on peanut (Arachis hypogaeal L.) growth and production - Christa Dyah Utami; almuzaki, Naufal Daffa almuzaki (International Integrated Agricultural Journal (IIAJ), 2025)
Peanuts are plants that are included in the secondary crops. However, the application of inorganic phosphorus fertilizer with continuous use can reduce soil quality, thereby reducing the yield of peanut harvests. The use of Pseudomonas fluorescens bacteria can increase phosphate absorption in peanuts so that it can reduce the dose of inorganic P fertilizer. This study was conducted from August to November 2024. Using the non-factorial RBD (randomized block design) method with Pseudomonas fluorescens bacterial concentration treatment consisting of control (without concentration), 20 ml/l, 30 ml/l, 40 ml/l, 50 ml/l, and 60 ml/l and a reduction of ¼ dose of SP-36 fertilizer. The parameters observed included plant height, dry biomass weight, fresh pod weight per sample, dry pod weight per sample, dry seed weight per plot, weight of 100 seeds, and number of root nodules. The results will be analyzed using ANOVA analysis of variance and DMRT further test. The administration of Pseudomonas fluorescens with a concentration of 50 ml/l + 75 kg/ha can provide a significant difference in the parameters of fresh pod weight per sample of 106.1 g and a concentration of 30 ml/l + 75 kg/ha affects the weight of dry pods weighing 71.60 g, dry seed weight of 648.8 g, weight of 100 seeds with a total of 57.95 g, and the number of root nodules of 24.21. For the parameters of plant height and dry biomass weight showed insignificant results.